Apolipoprotein E Allele and Hearing Thresholds in Older Adults. (February 2016) - Mener, David J.; Betz, Joshua; Yaffe, Kristine; Harris, Tamara B.; Helzner, Elizabeth P.; Satterfield, Suzanne; Houston, Denise K.; Strotmeyer, Elsa S.; Pratt, Sheila R.; Simonsick, Eleanor M.; Lin, Frank R.
Background: Whether apolipoprotein E (APOE) E4 allele status which is associated with an increased risk of cognitive decline is also associated with hearing impairment is unknown. Methods: We studied 1833 men and women enrolled in the Health, Aging and Body Composition study. Regression models adjusted for demographic and cardiovascular risk factors were used to assess the cross-sectional association of APOE-E4 status with individual pure tone hearing thresholds and the 4-frequency pure tone average (0.5-4 kHz) in the better hearing ear. Results: Compared to participants with no APOE-E4 alleles, participants with 1 allele had better thresholds at 4.0 kHz (β = −2.72 dB, P = .013) and 8.0 kHz (β = −3.05 kHz, P = .006), and participants with 2 alleles had better hearing thresholds at 1.0 kHz (β = −8.56 dB, P = .021). Conclusion: Our results suggest that APOE-E4 allele status may be marginally associated with better hearing thresholds in older adults.